2010
DOI: 10.1158/1055-9965.epi-10-0246
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Menarche and First Birth in Relation to Risk of Breast Cancer in A-Bomb Survivors

Abstract: Background: The length of the interval between age at menarche and age at first birth is positively associated with breast cancer risk. We examined the risk of breast cancer in atomic bomb survivors to investigate whether women exposed to radiation between menarche and first birth had a higher risk of radiogenic breast cancer than women exposed at the same age but outside this interval.Methods: Women (n = 30,113) were classified into three reproductive status at the time of the bombings (ATB) categories (preme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Breast tissue is largely undifferentiated and exposed to the mitogenic effects of ER and PR during this period, and is thus particularly susceptible to carcinogens . The interval between menarche to first live birth has been described as a “window of high susceptibility.” A shorter interval from menarche to first live birth is linked to higher endogenous hormone levels . A French prospective cohort study reported that the risk of breast cancer for women in the highest quartile of cumulative number of menstrual cycles before first birth was 1.42‐fold higher .…”
Section: Discussionmentioning
confidence: 99%
“…Breast tissue is largely undifferentiated and exposed to the mitogenic effects of ER and PR during this period, and is thus particularly susceptible to carcinogens . The interval between menarche to first live birth has been described as a “window of high susceptibility.” A shorter interval from menarche to first live birth is linked to higher endogenous hormone levels . A French prospective cohort study reported that the risk of breast cancer for women in the highest quartile of cumulative number of menstrual cycles before first birth was 1.42‐fold higher .…”
Section: Discussionmentioning
confidence: 99%
“…Among Japanese A-bomb survivors, parity, first full-term pregnancy at a young age, multiple births and history of breastfeeding have all been shown to be associated with a lower excess risk of breast cancer after radiation exposure (13). A recent study of Japanese atomic bomb survivors, however, found that once the baseline breast cancer risk was taken into account, radiation-induced breast cancer risk did not vary appreciably by whether exposure occurred before menarche, between menarche and first pregnancy, or after first pregnancy, i.e., radiation-associated breast cancer risk did not vary by reproductive status at the time of exposure (16). …”
Section: Discussionmentioning
confidence: 99%
“…However, this may be due to misclassification of menopausal status as opposed to an important biological effect involving menarche status at the time of radiation exposure. McDougall et al found no association of breast cancer risk and menarche status at the time of radiation exposure but did not consider serum marker levels 38.…”
Section: Discussionmentioning
confidence: 99%